Fecal Calprotectin: Beyond a Biomarker of Intestinal Inflammation: From Diagnostic Tool to a Link Between Gut, Immunity, and Systemic Disease - Bronikowski, Kamil; Ryszkowski, Maksymilian; Fornal, Krystian; Będkowska-Kuśmierek, Natalia; Zaborowska, Sabina; Pawlak, Paulina; Wojcieszuk, Olaf; Starczewski, Łukasz; Babik, Adrianna; Kamińska, Kamila (Journal of Education, Health and Sport, 2026)
Background. Fecal calprotectin (FC), a neutrophil-derived S100A8/S100A9 heterodimer, is a widely used non-invasive biomarker of intestinal inflammation, particularly in inflammatory bowel diseases (IBD). Emerging evidence suggests its broader role in gut barrier dysfunction and systemic inflammation. Aim. To evaluate the clinical relevance of fecal calprotectin, focusing on its diagnostic performance, limitations, and emerging applications beyond IBD. Material and methods. A narrative review of PubMed-indexed literature was conducted, including original studies and reviews addressing the biological role of calprotectin, its diagnostic accuracy, and its association with intestinal permeability, microbiota, and metabolic inflammation. Results. Fecal calprotectin demonstrates high sensitivity for detecting intestinal inflammation and is useful in differentiating IBD from functional disorders such as irritable bowel syndrome. Its levels correlate with disease activity and are valuable in monitoring treatment response and predicting relapse. However, its specificity is limited, as elevated levels may occur in infections, malignancies, and drug-related mucosal injury. Recent studies suggest associations between FC, gut microbiota alterations, and low-grade systemic inflammation. Conclusions. Fecal calprotectin is a valuable tool in the diagnosis and management of intestinal inflammation. Its expanding role in systemic conditions highlights the need for further research to improve standardization and clarify its clinical applications